Brachial-Ankle Pulse Wave Velocity Predicts New-Onset Hypertension and the Modifying Effect of Blood Pressure in a Chinese Community-Based Population. (13th April 2020) - Jiang, Yimeng; Fan, Fangfang; Jia, Jia; Li, Jianping; Xia, Yulong; Zhou, Jing; Huo, Yong; Zhang, Yan
Abstract : Brachial-ankle pulse wave velocity (baPWV) was proven to be a prognostic indicator of cardiovascular events. However, the modifying effect of blood pressure (BP) on the longitudinal association between baPWV and new-onset hypertension is not well established. This study included 1849 non-hypertensive Chinese subjects from Shougang cohort study during December 2011 to July 2014. BaPWV was obtained using an Omron Colin BP-203RPE III device. Multivariate logistic regression models were used to evaluate associations of baPWV and outcomes. During a mean follow-up time of 2.36 years, 248 (13.41%) developed hypertension. BaPWV independently and gradably predicted the risk of incident hypertension and the SBP level at revisit (odds ratio or β (95% confidence interval) for participants with baPWV in quartile 4 vs. quartile 1: 2.72 (1.54, 4.78) for incident hypertension and 5.92 (4.26, 7.58) for SBP, P for trend: <0.001) after adjusting demonstrated risk factors. Besides, the effects of baseline baPWV on either incident hypertension or SBP at revisit were interactively modified by the level of baseline SBP; the effect size increased as the SBP level decreased. baPWV independently predicted the risk of hypertension and BP progression, modified by the level of SBP at baseline in this Chinese community-based population. The combination of baPWV and SBP can help differentiate the potential high-risk candidates who will develop hypertension quickly and benefit from early diagnosis and treatment.